Makna Kerja sebagai Prediktor Work Engagement pada Karyawan Tekstil - Muhammad Aufa Al Farisi Ann Haba Sauda; Umi Anugerah Izzati (Yayasan Literasi Sains Indonesia, 2025)
The Indonesian textile and textile product (TPT) industry faces serious challenge due to significant export performance decline, demanding companies to strengthen employee performance as strategic asset. This research aims to identify the significance of relationship between work meaningfulness and work engagement on production employees of textile company. Using quantitative approach with correlational design, the research involves 72 production employees of Company X who were selected through simple random sampling. Data was collected using work meaningfulness scale that was developed based on the concept of Steger (2019) and work engagement based on the concept of Schaufeli and Bakker (2010), which then was analyzed using Pearson Product Moment correlation. Research results show significant positive relationship between work meaningfulness with work engagement (r = 0.406, p < 0.05), with contribution amounting to 16.4% toward work engagement variance. This finding confirms work meaningfulness plays role as work resource that strengthens work engagement of production employees in the context of TPT industry, in alignment with Job Demands-Resources (JD-R) Model. The practical implication of this research suggests human resource management to increase work engagement through strengthening perception of work meaningfulness, particularly by clarifying work contribution toward organizational goals and wide society.